Por una perspectiva crítica de la salud - Natteri Romero, Iván Adolfo (2025)
In a restricted way, health is understood as the absence of disease.  This positivist approach omits lifestyles and their ways of reproducing themselves, which would imply incorporating the social, historical and political processes that corporality goes through.  The aim of this research is to carry out this criticism.